My little phony : a Clique novel - Harrison, Lisi (Harrison, Lisi. Clique., 2010)
As the holidays approach, Massie, Alicia, Dylan, Kristen, and Claire deal with budget woes, boy friends and each other in the continuing adventures of the Clique.